PERUBAHAN KEBIJAKAN NUKLIR IRAN DI ERA PEMERINTAHAN HASSAN ROUHANI - Resty Meiva Rizky; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aimed to describe the changing of Iran nuclear policy era President Hassan Rouhani. This research aims to look at the different policy of the President Iran, be-tween Mahmoud Ahmadinejad (2005-2013) and Hassan Rouhan 2013-present). In 2012, Mahmoud Ahmadinejad has rejected the agreement with P5+1 (America, Russia, England, France, China plus Germany) to stop their uranium enrichment. It cause some sanctions for Iran from United Nations Security Council. The the impact of sanctions on Iran including high inflation, low growth, and coagulation asset in foreign state.The perspective that applied in this research is behavioralist , level analysis of indi-vidual, and also use theory from William D. Coplin about of foreign policy-making, there are three things to be considered by a leader in taking a foreign policy; the domestic political conditions, economic and military conditions, and international context.Hassan Rouhani as a new president of Iran tries to rebuild the economy of Iran, by undertake a nuclear talks with P5+1 state. These negotiations resulted an interim deal for six months (since November 2013 until May 2014). Which Iran agreed to suspend uranium enrichment, willing to dilute the uranium up to five percent of maximum limit, and not build-ing new centrifuges for uranium enrichment. In return, Iran would get liquefaction in foreign asset amounted to US$ 7 billion, their right to export and import oil, and acknowledgment in their nuclear for peace programme.Keywords: Behavioralist, foregin policy-making, Iran, nuclear, P5+1